Gut microbiota composition associated with hepatic fibrosis in non‐obese patients with non‐alcoholic fatty liver disease. Issue 8 (29th March 2021) - Iwaki, Michihiro; Kessoku, Takaomi; Ozaki, Anna; Kasai, Yuki; Kobayashi, Takashi; Nogami, Asako; Honda, Yasushi; Ogawa, Yuji; Imajo, Kento; Yoneda, Masato; Maeda, Ayako; Tanaka, Yoshiki; et al.
Abstract: Background and Aim: Gut microbiota composition is associated with the pathogenesis of non‐alcoholic fatty liver disease. However, the association between gut microbiota composition and non‐alcoholic fatty liver disease in non‐obese patients remains unclear. We compared clinical parameters and gut microbiota profiles of healthy controls and non‐obese and obese patients with non‐alcoholic fatty liver disease. Methods: We examined the clinical parameters and gut microbiota profiles by 16S rRNA sequences and short‐chain fatty acid levels in fecal samples from 51 non‐obese patients with non‐alcoholic fatty liver disease (body mass index <25 kg/m 2 ) and 51 obese patients with non‐alcoholic fatty liver disease (body mass index ≥30 kg/m 2 ) who underwent pathological examination and 87 controls at five hospitals in Japan. Results: Although no significant differences between the non‐obese and other groups were observed in alpha diversity, a significant difference was found in beta diversity. We observed a significant decrease in serum alanine aminotransferase levels, Eubacterium population, and butyric acid levels in non‐obese patients with non‐alcoholic fatty liver disease compared with those in obese patients with non‐alcoholic fatty liver disease. A significant negative correlation was found between the stage of hepatic fibrosis and Eubacterium abundance in non‐obese patients with non‐alcoholic fatty liver disease. Conclusions: The decrease in the abundance of Eubacterium that produces butyric acid may play an important role in the development of non‐alcoholic fatty liver disease in non‐obese individuals. This study was registered at the University Hospital Medical Information Network clinical trial registration system (UMIN000020917).